2019
DOI: 10.1186/s41938-019-0187-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the combined antifungal potential of Trichoderma spp. and organic amendments against dry root rot of mungbean

Abstract: The present study was carried out to evaluate the effect of bioagents and organic amendments in suppressing the dry root rot of mungbean incited by Rhizoctonia bataticola. The locally isolated pathogen and fungal biocontrol agents were identified based on morphological and molecular characterization. These identified bioagents were tested in vitro, and the highest mycelial inhibition was recorded in dual culture assay by Trichoderma harzianum (74.44%), and among organic amendments, maximum mycelial inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…In this study, T. phayaoense could reduce the degree of mycelial growth of S. cucurbitacearum and F. equiseti in the dual culture assay through the parasitism effect. These results are similar to those of previous studies (Ru and Di, 2012;Sánchez-García et al, 2017;Chounhary and Ashraf, 2019;Haque et al, 2020) which reported that the Trichoderma species could inhibit the mycelial growth of several plant pathogenic fungi by the parasitism, antifungal production, and a competition for space and nutrients. Additionally, the inhibition efficiency was varied among Trichoderma species and strains, as well as being dependent upon the species of fungal plant pathogens (Hermosa et al, 2012;Ru and Di, 2012;Dawidziuk et al, 2016;Bunbury-Blanchette and Walker, 2019;Haque et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, T. phayaoense could reduce the degree of mycelial growth of S. cucurbitacearum and F. equiseti in the dual culture assay through the parasitism effect. These results are similar to those of previous studies (Ru and Di, 2012;Sánchez-García et al, 2017;Chounhary and Ashraf, 2019;Haque et al, 2020) which reported that the Trichoderma species could inhibit the mycelial growth of several plant pathogenic fungi by the parasitism, antifungal production, and a competition for space and nutrients. Additionally, the inhibition efficiency was varied among Trichoderma species and strains, as well as being dependent upon the species of fungal plant pathogens (Hermosa et al, 2012;Ru and Di, 2012;Dawidziuk et al, 2016;Bunbury-Blanchette and Walker, 2019;Haque et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…1. Similar result was found by Choudhary and Ashraf (2019), Gnanaprakash et al, (2015), Sangeetha and Jahagirdar (2013) where they showed that Trichoderma viride and neem can be recommended as an effective approach for the management of dry root rot. The Results revealed that there was significant difference between the treatments and maximum plant height (38.66cm), number of branches (9.80), root length (9.6), no.…”
Section: Resultssupporting
confidence: 81%
“…This may be due to the synergistic effect of chemical control by fungicide along with the use of bio agent and organic amendment. The findings are in agreement with several studies (Sindhu keerthana et al, 2022;Karthikeyan et al, 2006;Manjunatha et al 2011;Nageswararao et al, 2012;Kumar et al, 2015;Choudhary andAshraf, 2019 andGaikwad et al, 2020) which reported enhanced disease control of dry root rot and stem rot in groundnut when organic amendments, fungicides and bio agents were integrated. Also the results of studies conducted by various workers on different crops (Latha et al, 2017in black gram, Thilagavathi et al, 2007in green gram, Rajkumar et al, 2019Manjunatha et al, 2011and Deepa et al, 2018in chickpea, Dhawan et al, 2019in soybean, Adhikary et al, 2019 in sesame) for the management of R. bataticola have indicated that the integration of chemical, biological and organic measures not only has provided better control of the disease but also enhanced the crop growth and yield when compared to the use of only one of the management measures.…”
Section: No Of Pods Per Plant and Pod Yieldsupporting
confidence: 92%